The relation between overreaction in forecasts and uncertainty: A nonlinear approachvon - Julian Sebastian Leppin (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2014)
This paper examines if overreaction of oil price forecasters is related to uncertainty. Furthermore, it takes into account impacts from oil price return and oil price volatility on forecast changes. The panel smooth transition regression model from González et al. (2005) is applied with different specifications of the transition functions to account for nonlinear relations. Data on oil price expectations for different time horizons are taken from the European Central Bank Survey of Professional Forecasters. The results show that forecast changes are governed by overreaction. However, overreaction is markedly reduced when high levels of uncertainty prevail. On the other hand, noisy signals and positive oil price returns tend to cause higher overreaction.
Keywords: G14; C33; E37; 330; Overreaction; Uncertainty; Panel Smooth Transition Regression